PELAKSANAAN PROGRAM SOSIALISASI KONSERVASI PESUT MAHAKAM OLEH WWF INDONESIA DI KECAMATAN PENYINGGAHAN - Rizki Tegar Sembada (LP2M Universitas Sarjanawiyata Tamansiswa, 2019)
AbstractPesut mahakam is a typical endemic animal of East Kalimantan that experienced a decline in population due to the ecosystem environment is threatened. WWF Indonesia as a branch of the international environmental organization is intrigued and wants to save the endangered animals by conducting a conservation awareness program of Pesut Mahakam in the core habitat of this animal, there is a core location that is allegedly become the habitat of mahakam dolphins ie Sub-District Penyinggahan in West Kutai Regency. This research aims to convey information about the conservation of Pesut Mahakam and the future step in terms of practices to encourage participation and active participation of the community in carrying out the conservation program. This research uses qualitative method and analytical technique used is qualitative interactive. The results of this study explain the result of conservation conducted by WWF Indonesia that is the creation of Kampung Hijau, a pilot village in maintaining and building a beautiful and healthy environment and as a role model is expected to restore the environment cashew habitat where the Pesut Mahakam live.Â Keyword : Pesut Mahakam, WWF of Indonesia, conservation socialization